Sharp Weighted Bounds for Multilinear Fractional Type Operators Associated with Bergman Projection. (3rd June 2018) - Zhang, Juan; Lan, Senhua; Xue, Qingying
Abstract : We first introduce the multiple weights which are suitable for the study of Bergman type operators. Then, we give the sharp weighted estimates for multilinear fractional Bergman operators and fractional maximal function.